The human thymus microenvironment: in vivo identification of thymic nurse cells and other antigenically-distinct subpopulations of epithelial cells. - Ritter, M A (1981)
We have studied the human thymus microenvironment in order to identify subsets of cells that may be responsible for the induction of different aspects of T-lymphocyte differentiation, education and MHC restriction. Using immunofluorescence on tissue sections and cell suspensions we have found MHC products (HLA-A, B, C and DR) to be present throughout the thymus epithelium whilst human T-cell antigens are absent from all non-lymphoid cells. In contrast, Thy-1 antigen (expressed on approximately 1% paediatric human thymocytes) has a differential expression amongst thymic epithelial cells, being confined to those in the subcapsular cortex and to 'thymic nurse cells' (TNC). The former represent the site to which thymocyte precursors first migrate upon entering the thymus. The latter are large epithelial cells, located within the cortex, whose plasma membrane totally enclose a number of thymus lymphocytes; these cells are therefore good candidates for the mediators of direct contact (stromal) induced thymocyte maturation.